Ball and Hoop System Control Position Using LQG Technique - Ahmed Mohamed Altnazfti; Adel Abobker Ehmied; Ali S. Zayed; Najeh Ibrahim Allafi; Ibrahim Mohammed Al Tanazfti (African Journal of Advanced Pure and Applied Sciences, 2023)
The aim of this paper is to compare the performance between two types of control systems (Ball and Hoop system). It can be used to analyze the dynamic of fluid problems. As soon as the goal from that to identify a control strategy that offers the best performance in controlling the position of the ball and hoop system. However, the LQG controller designed and compared their performance with the Linear Quadratic LQR controller using MATLAB and Simulink. The results showed that the performance response of LQG controller better than the LQR control strategy response. Therefore, the performance response of the proposed system was tested and compared with the results of PID as a reference tracking rejection and disturbance behavior. The simulation results showed that the proposed controller has better performance and lower stability time compared to the traditional PID controller. we hope in the future using high technology to this work.